Historitas Perkembangan Al-Qawaid Al-Asasiyah Dalam Literatur Qawa’id Fiqihiyah - Jeeny Rahmayana; Agustri; Nanang Wartono (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
The purpose of this paper is to present the historical development of the main fiqh rules (al-Qawaid al-Asasiyah) in the literature of Qawaid Fiqihiyah. In various qawa'id fiqihiyah literature, various kinds of fiqh rules, generally arranged with a systematic First, the main fiqh rules (al-qawaid al-asasiyah). Called the parent, because many branch rules that can be returned or projected to him. Second, the rules of branch fiqh agreed upon by the majority of scholars. Third, the rules of branch fiqh that are disputed by the scholars. The methodology or approach used in this paper uses a method or approach to literature (library research), while data collection is done by reviewing and / or exploring several journals, books, and other documents both in print and electronic form, as well as other sources of data and / or information that are considered relevant to the study. The findings in this study are that the main fiqh rules, quantitatively or in number, are still disputed by the scholars. As-Suyuthi argued that al-Qadhi Abu Sa'id returned all issues of the Shafi'i madhhab to the four main legal rules. Shaykh Izzudin Ibn Abd al Salam, said that all fiqh issues can be returned to i'tibar al-mashalih alone. Because dar'u al-mafasid is part of i'tibar al-mashalih. But the majority of scholars are of the opinion that this master fiqh rule has five propositions.